Justification of choosing a reasonable distance between the driver’s cabin and the semi-trailer to reduce the aerodynamic resistance of the vehicle - Beherskyi, Dmytro; Vitiuk, Ivan; Koval, Andrii; Golubovskyi, Andrii; Perehuda, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the aerodynamic resistance of a main road train and its influence on the efficiency of the transportation process. Reducing the aerodynamic resistance of road trains is an important problem, since fuel consumption and transportation efficiency depend on it. A 2 % reduction in aerodynamic drag reduces fuel consumption by 1 %. Reduction of aerodynamic resistance is achieved by using special aerodynamic devices. But their use creates a number of problems – an increase in the weight of the road train and its overall dimensions, etc. It is assumed that by choosing a rational distance between the cab and the semi-trailer of the road train, it is possible to significantly reduce fuel consumption. The obtained results show that the total aerodynamic resistance of the road train significantly depends on the distance between the driver’s cabin and the semi-trailer. This is explained by the fact that in the space between the cabin and the semi-trailer, vortices of the air flow occur, which leads to an increase in aerodynamic resistance. The resulting dependence of excess pressure in the space between the cabin and the semi-trailer on the distance between them makes it possible to determine two ranges of distances where this pressure will be minimal. In contrast to known studies, the results of the modeling make it possible to establish a rational distance between the cab and the semi-trailer of the road train from the point of view of obtaining the minimum total aerodynamic resistance. However, changing the distance between the cab and the semi-trailer can affect the controllability and stability of the road train. The obtained results can be used in the development of semi-trailer structures, which will ensure a reduction of the total aerodynamic resistance of road trains. And this will lead to a decrease in fuel consumption for the transportation process